Misalignment and Perverse Incentives: Examining the Politics of District Leaders as Brokers in the Use of Research Evidence. (March 2014) - Daly, Alan J.; Finnigan, Kara S.; Jordan, Stuart; Moolenaar, Nienke M.; Che, Jing
In the current accountability policy context, access to and use of research evidence are central to district and school improvement. Our study examines the network of relations between central office administrators and principals using a political lens to consider the ways in which the underlying politics in a district may call into question some of the assumptions around evidence use and change under accountability policy sanctions. Results indicate that relational ties regarding evidence use (data use in this case) are sparse in comparison with other work-related networks. Second, we find a misalignment between what one would expect based on district data use initiatives, formal lines of authority, and communication patterns and the underlying informal social interactions of the leaders around the use of data. We discuss the implications of this research for district improvement and the use of evidence in the current policy context.